Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Cherry Ngọc
Xem chi tiết
Cherry Ngọc
Xem chi tiết
Cherry Ngọc
Xem chi tiết
Bích Ngọc
Xem chi tiết
Nguyễn Lê Phước Thịnh
20 tháng 5 2022 lúc 22:11

 

undefined

Bích Ngọc
Xem chi tiết
Nguyễn Lê Phước Thịnh
20 tháng 5 2022 lúc 21:55

a: Sửa đề: \(\dfrac{2x-1}{11}+\dfrac{2x-2}{12}+\dfrac{2x-3}{13}=\dfrac{2x+5}{5}+\dfrac{2x+7}{3}+\dfrac{2x+4}{6}\)

\(\Leftrightarrow\dfrac{2x-1}{11}+1+\dfrac{2x-2}{12}+1+\dfrac{2x-3}{13}+1=\dfrac{2x+5}{5}+1+\dfrac{2x+7}{3}+1+\dfrac{2x+4}{6}+1\)

=>2x+10=0

hay x=-5

b: \(\dfrac{x-1}{2016}+\dfrac{x-2}{2015}+\dfrac{x-3}{2014}+\dfrac{x-4}{2013}+\dfrac{x-5}{2012}-5=0\)

\(\Leftrightarrow\left(\dfrac{x-1}{2016}-1\right)+\left(\dfrac{x-2}{2015}-1\right)+\left(\dfrac{x-3}{2014}-1\right)+\left(\dfrac{x-4}{2013}-1\right)+\left(\dfrac{x-5}{2012}-1\right)=0\)

=>x-2017=0

hay x=2017

Bích Ngọc
Xem chi tiết
Nguyễn Lê Phước Thịnh
20 tháng 5 2022 lúc 21:55

a: Sửa đề: \(\dfrac{2x-1}{11}+\dfrac{2x-2}{12}+\dfrac{2x-3}{13}=\dfrac{2x+5}{5}+\dfrac{2x+7}{3}+\dfrac{2x+4}{6}\)

\(\Leftrightarrow\dfrac{2x-1}{11}+1+\dfrac{2x-2}{12}+1+\dfrac{2x-3}{13}+1=\dfrac{2x+5}{5}+1+\dfrac{2x+7}{3}+1+\dfrac{2x+4}{6}+1\)

=>2x+10=0

hay x=-5

b: \(\dfrac{x-1}{2016}+\dfrac{x-2}{2015}+\dfrac{x-3}{2014}+\dfrac{x-4}{2013}+\dfrac{x-5}{2012}-5=0\)

\(\Leftrightarrow\left(\dfrac{x-1}{2016}-1\right)+\left(\dfrac{x-2}{2015}-1\right)+\left(\dfrac{x-3}{2014}-1\right)+\left(\dfrac{x-4}{2013}-1\right)+\left(\dfrac{x-5}{2012}-1\right)=0\)

=>x-2017=0

hay x=2017

lucas R.
Xem chi tiết
Nguyễn Lê Phước Thịnh
21 tháng 3 2021 lúc 13:05

Sửa đề: \(\dfrac{x+2}{2014}+\dfrac{x+1}{2015}=\dfrac{x+2001}{15}+\dfrac{x+2014}{2}\)
Ta có: \(\dfrac{x+2}{2014}+\dfrac{x+1}{2015}=\dfrac{x+2001}{15}+\dfrac{x+2014}{2}\)

\(\Leftrightarrow\dfrac{x+2}{2014}+1+\dfrac{x+1}{2015}+1=\dfrac{x+2001}{15}+1+\dfrac{x+2014}{2}+1\)

\(\Leftrightarrow\dfrac{x+2016}{2014}+\dfrac{x+2016}{2015}=\dfrac{x+2016}{15}+\dfrac{x+2016}{2}\)

\(\Leftrightarrow\dfrac{x+2016}{2014}+\dfrac{x+2016}{2015}-\dfrac{x+2016}{15}-\dfrac{x+2016}{2}=0\)

\(\Leftrightarrow\left(x+2016\right)\left(\dfrac{1}{2014}+\dfrac{1}{2015}-\dfrac{1}{15}-\dfrac{1}{2}\right)=0\)

mà \(\dfrac{1}{2014}+\dfrac{1}{2015}-\dfrac{1}{15}-\dfrac{1}{2}\ne0\)

nên x+2016=0

hay x=-2016

Vậy: S={-2016}

Mavis Vermilion
Xem chi tiết
Trần Phương Linh
Xem chi tiết
Lê Trang
20 tháng 7 2021 lúc 10:43

\(P\left(0\right)=a\cdot0^3+b\cdot0^3+c\cdot0+d=2017\)

\(\Leftrightarrow d=2017\)

\(P\left(1\right)=a\cdot1^3+b\cdot1^2+c\cdot1+d=2\)

\(\Leftrightarrow a+b+a+d=2\)

\(P\left(-1\right)=a\cdot\left(-1\right)^3+b\cdot\left(-1\right)^2+c\cdot\left(-1\right)+d=6\)

\(\Leftrightarrow-a+b-c+d=6\)

\(P\left(2\right)=a\cdot2^3+b\cdot2^2+c\cdot2+d=-6033\)

\(\Leftrightarrow8a+4b+2c+d=-6033\)